2020
DOI: 10.1037/ccp0000499
|View full text |Cite
|
Sign up to set email alerts
|

Applying experimental therapeutics to examine cognitive and chronological vulnerabilities as mediators of acute outcomes in cognitive-behavioral therapy and light therapy for winter depression.

Abstract: Objective: We applied the experimental therapeutics approach to test whether acute treatment outcomes for winter seasonal affective disorder (SAD) are mediated by a cognitive mechanism in cognitive–behavioral therapy (CBT-SAD) versus a chronobiologic mechanism in light therapy (LT). Method: Currently depressed adults with major depression, recurrent with seasonal pattern (N = 177; 83.6% female, 92.1% non-Hispanic White, M age = 45.6) were randomized to 6 weeks of LT or group CBT-SAD. SAD symptoms were assessed… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
5
1
1

Relationship

2
5

Authors

Journals

citations
Cited by 8 publications
(4 citation statements)
references
References 49 publications
0
4
0
Order By: Relevance
“…Third, future studies on cognitive change should explicitly measure different levels of cognitive change. When we compare our findings on dysfunctional thinking with recent other studies that investigated potential mediation of cognitive change in CBT for depression, the other study that found significant mediation of cognitive change specific to CBT (compared to light therapy) also used a measure of automatic negative thoughts (Rohan, Burt, Camuso, Perez, & Meyerhoff, 2020), while two other studies that did not find mediation or any temporal effects, but did show that dysfunctional attitudes decreased in all treatment conditions, did measure cognitive change with a measure of dysfunctional attitudes (Lemmens et al, 2017;Quigley et al, 2019). Future studies should take into account that different levels of cognitive change (automatic thoughts, dysfunctional attitudes, core beliefs or schemas) may play different roles within psychotherapy for depression.…”
Section: Tablementioning
confidence: 72%
“…Third, future studies on cognitive change should explicitly measure different levels of cognitive change. When we compare our findings on dysfunctional thinking with recent other studies that investigated potential mediation of cognitive change in CBT for depression, the other study that found significant mediation of cognitive change specific to CBT (compared to light therapy) also used a measure of automatic negative thoughts (Rohan, Burt, Camuso, Perez, & Meyerhoff, 2020), while two other studies that did not find mediation or any temporal effects, but did show that dysfunctional attitudes decreased in all treatment conditions, did measure cognitive change with a measure of dysfunctional attitudes (Lemmens et al, 2017;Quigley et al, 2019). Future studies should take into account that different levels of cognitive change (automatic thoughts, dysfunctional attitudes, core beliefs or schemas) may play different roles within psychotherapy for depression.…”
Section: Tablementioning
confidence: 72%
“…As an advantage over symptom-based measures for distinguishing SAD versus nonseasonal MDD, seasonal beliefs, as measured by the SBQ, represent a malleable treatment target and potentially a cognitive vulnerability to SAD. A recent clinical trial comparing CBT-SAD to light therapy in 177 adults with SAD found evidence that seasonal beliefs mediate acute outcome in CBT-SAD (Rohan et al, 2020). Using parallel-process growth models, CBT-SAD promoted greater decreases in SBQ scores during treatment than light therapy, and these changes were related to decreases in symptoms only in CBT-SAD (Rohan et al, 2020).…”
Section: Discussionmentioning
confidence: 99%
“…A recent clinical trial comparing CBT-SAD to light therapy in 177 adults with SAD found evidence that seasonal beliefs mediate acute outcome in CBT-SAD (Rohan et al, 2020). Using parallel-process growth models, CBT-SAD promoted greater decreases in SBQ scores during treatment than light therapy, and these changes were related to decreases in symptoms only in CBT-SAD (Rohan et al, 2020). In contrast, depressogenic attitudes (DAS scores) improved comparably during CBT-SAD and light therapy, and the DAS did not mediate acute outcome in CBT-SAD.…”
Section: Discussionmentioning
confidence: 99%
“…Seasonal beliefs distinguish between individuals with SAD vs. non-seasonal unipolar depression (32,33). Seasonal beliefs change significantly more over the course of CBT-SAD than during LT, and greater change towards more flexible seasonal beliefs during treatment mediates both improvements in depression symptoms during active treatment (34) and lower depression scores one and two winters following treatment (35). This provides evidence that engagement of the seasonal beliefs target mediates CBT-SAD's acute antidepressant effects and its enduring benefits over LT.…”
Section: Cbt-sad Effectively Treats Sad Lowers Risk Of Recurrence And...mentioning
confidence: 99%